Maternal environmental factors influencing kochia (Kochia scoparia) seed characteristics - Esser, Andrew Ross (Kansas State University, 2014)
A better understanding of kochia (Kochia scoparia) seed characteristics is necessary for long term management of this increasingly troublesome weed. The objectives were to evaluate maternal environmental factors influencing kochia seed produced in the field and to document variability in dormancy and seed viability produced within a single kochia plant grown in the greenhouse or field. Field experiments were conducted in 2012 and 2013 at the Kansas State Agricultural Research Center in Hays. Two different kochia biotypes from Hays were planted with and without five canopy types, namely corn, soybean, grain sorghum, wheat stubble, and kochia plants. A greenhouse experiment with two generations (F1 and F2) of self-pollination was conducted with the same kochia biotypes. Date of initial flowering and final plant heights were recorded. Plants were harvested when seed was mature and divided into three equal parts (top, middle, and bottom). Seeds were cold treated or not, and approximately 50 seeds were placed in petri dishes with water for germination counts taken over six weeks. Viability of remaining seeds were then tested. For field-grown kochia, plants were taller in corn, sorghum and weedy canopies compared to the absence of a canopy. Seed germination from field grown kochia ranged between 77 and 100% for both treatments. There was reduced germination in the presence of a weedy canopy for both treatments and biotypes (77 to 82%) compared to the absence (93 to 99%), with an increase in hard viable seed in the presence of weedy canopy (5 to 14%). In the greenhouse, the F2 generation produced more immediately germinable seed compared to the F1 generation which had more seed with delayed germinability. Seed from bottom third of F1 and F2 plants had greater total germination (73 and 70%, respectively) compared to the middle (61 and 65%) and top (50 and 59%) thirds of the plant. There was a maternal environmental effect on kochia seed characteristics with implications on generating persistent seed for the future seedbank.
Keywords: Kochia scoparia; Seed dormancy; Seed germination; Crop-weed competition; Agronomy (0285)